(untitled) (Journal of the College of Basic Education, 2024)
The research deals with drifts velocities of the solar wind particles at corona region with distance ranging between 1 to 15Rʘ for different values of angles. It has been examined, that drifts velocities in parker spiral model within single particle motion model, in spherical coordinates system (local coordinate system within axis parallel to the magnetic field). In this research, it was found that, the grad B drift velocity has high result at pole region and have been getting only the slow solar wind proton with value reach to108 m/sec. and the fast solar wind vanished.